Bleomycin induces epithelial-to-mesenchymal transition via bFGF/PI3K/ESRP1 signaling in pulmonary fibrosis. Issue 1 (14th January 2020) - Weng, Chang-Mei; Li, Qing; Chen, Kui-Jun; Xu, Cheng-Xiong; Deng, Meng-Sheng; Li, Tao; Zhang, Dong-Dong; Duan, Zhao-Xia; Chen, Zhi-Qiang; Li, Guan-Hua; Chen, Jing; Wang, Jian-Min
Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal and chronic disease with a high rate of infection and mortality; however, its etiology and pathogenesis remain unclear. Studies have revealed that epithelial–mesenchymal transition (EMT) is a crucial cellular event in IPF. Here, we identified that the pulmonary fibrosis inducer bleomycin simultaneously increased the expression of bFGF and TGF-β1 and inhibited epithelial-specific regulatory protein (ESRP1) expression in vivo and in vitro . In addition, in vitro experiments showed that bFGF and TGF-β1 down-regulated the expression of ESRP1 and that silencing ESRP1 promoted EMT in A549 cells. Notably, we determined that bFGF activates PI3K/Akt signaling, and treatment with the PI3K/Akt inhibitor LY294002 inhibited bleomycin-induced cell morphology changes and EMT. In addition, the effects of LY294002 on bleomycin-induced EMT were inhibited by ESRP1 silencing in A549 cells. Taken together, these findings suggest that bleomycin induced EMT through down-regulating ESRP1 by simultaneously increasing bFGF and TGF-β1 in pulmonary fibrosis. Additionally, our findings indicated that bFGF inhibits ESRP1 by activating PI3K/Akt signaling.